The Applied Research of PID Controller Based on NN in Servo System - Fu, Xiao Juan; Wu, Hong Kun; Wu, Zhen Yuan (Applied Mechanics and Materials, 2015)
This paper design a PID controller based on nerve net aimed some servo system. The controller use NN control algorithm on the basis of classic PID controller. It can adjust the parameters of PID adaptively and realize the control demand of high precision and rapidity. The control algorithm is programmed using MATLAB and c++ language. According to results of the simulation and experiments, the NN PID controller has good static and dynamic property and meets the performance of actual servo system very well.